Parental Participation in Latin American Basic Education: A Systematic Review - Gubbins, Verónica (2025)
There is consensus among researchers about the benefits of parental involvement in primary school education. The empirical development available refers to research mainly developed in the countries of the northern hemisphere where educational inequalities are less visible than in Latin American countries. When it is integrated, it is not addressed in a differentiated way, which limits knowledge about the specificities and commonalities between its countries. The objective of this research is to analyze the Latin American scientific production that addresses the study of parental involvement in the field of primary school education, published between 2020 to 2024, following the methodological guidelines of Systematic Reviews. The review highlights the scarce and unequal production between countries where studies on parental involvement from a pedagogical and formative approach prevail. Following what has been described for the Spanish case and the Anglophone countries, the review shows the use of different concepts to refer to parental involvement. The few definitions found show distinctions between the notions of involvement, implication, connection between families and schools and parental participation, which shows a novel conceptual development compared to what is found in northern countries.